Improving the methods of interpreting electrical monitoring observations to identify areas of engineering geological complications - Khristenko, L.A.; Kichigin, E.I.; Parshakov, E.I.; Tainickiy, A.A. (Perm Federal Research Centre Journal, 2019)
The aim of the research was to increase the reliability and informativeness of the results of interpreting natural and artificial electric fields using wavelet transforms and methods of probabilistic- statistical approach. The obtained results showed that the use of wavelets allows us to identify and describe the hidden features of signals, to obtain convenient for the analysis of the presentation of graphs of values of apparent resistance, with different details of their consideration. The data obtained as a result of geologic-geophysical researches, owing to the objective reasons, can be considered a sample of one or several aleatory variables. This allows analyzing their statistical characteristics by means of the theory of estimates. Using the apparatus of the theory of assessments allows you to describe (in a formalized form), compare and divide into classes geological objects. The traditional interpretation of field measurement data of the natural field and electricoprofiling, most often based on qualitative analysis or on the simplest methods for estimating the depth and size of anomalous bodies, leads to ambiguous conclusions about the presence and nature of the phenomena that caused changes in the observed parameters. Objectivity of quantitative assessments gives fundamentally different results of interpretation of the observed objects and processes and helps to increase the reliability of conclusions about the geological nature of the occurrence of the phenomena and processes under study. New approaches to the interpretation of electrical profiling data have been created, which make it possible to significantly increase the amount of useful information, more clearly trace the features of the geological structure implicitly expressed in the observed fields and increase the accuracy of the forecast of catastrophic phenomena. A procedure has been developed for applying wavelet transform and classification procedures to effectively solve the problems of mapping the spatial boundaries of engineering-geological complications within areas of complex geologic-geophysical monitoring observations of potentially hazardous karst and man-made manifestations.